Increased prevalence of lymphoid tissue inducer cells in the cerebrospinal fluid of patients with early multiple sclerosis. (July 2016) - Degn, Matilda; Modvig, Signe; Dyring-Andersen, Beatrice; Bonefeld, Charlotte M; Frederiksen, Jette L; Geisler, Carsten; von Essen, Marina R
Background: Inflammatory cytokines produced by cells of the immune system are believed to play a central role in the pathogenesis of multiple sclerosis (MS). Innate lymphoid cells (ILCs) have been shown to produce and secrete a wide range of the cytokines involved in MS pathogenesis; however, a possible implication of ILCs in MS development and disease progression has not been investigated. Objective: With this study, we aimed to clarify a potential role of ILCs in the early stages of MS. Methods and Results: Using flow cytometry, we analysed the prevalence and phenotype of ILCs in the cerebrospinal fluid (CSF) of patients experiencing their first or second demyelinating event. We found a substantial increase in both frequency and number of ILCs, in particular the LTi subset, as compared to healthy controls. We also found an association between CSF pleocytosis and an increased frequency of LTi cells in the CSF, suggesting a favoured recruitment of blood derived LTi cells. Conclusion: Our data suggests a role for ILCs, and in particular the LTi subset, in the early stages of MS. This finding represents an important contribution to the understanding of early inflammation in MS, and adds new knowledge beneficial for future MS therapies.